SYNTHESIS, CHARACTERISATION AND APPLICATION OF PHENOL-FORMALDEHYDE RESIN BLENDED WITH SULPHONATED PHYLLANTHUS EMBLICA, LINN., CARBON - Seenivasan, R. K.; Ragavan, D.; Girija, A.; Muthuramalingam, R. (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
Phenol â€“ Formaldehyde Resin (PFR) is blended with Sulphonated Phyllanthus emblica, Linn., Carbon (SPEC) in various proportions by weight percentage (0-50%w/w). A few composite cation-exchangers were prepared by varying the amount of SPEC (a source of cheap and renevable plant material) in the blends from 10 to 50% (w/w). Reaction conditions for the preparation of blends were optimised. IR spectra, TGA traces, and SEM photos were taken for the characterization ofÂ resins. Physico-chemical, properties of the composite resins have been determined. The composites are insoluble in various solvents and reagents and stable towards heat.Â Â Cation exchange capacity (CEC) of the composite resins, decreased with the increasing percentage of SPEC in the blend. Thermodynamic equilibrium constants (lnK) are calculated for H+ - Zn2+ exchanges on the resins having a different amount of SPEC. Thermodynamic parameters are also calculated and suitable explanations are given. The composites up to 20% (w/w) blending retains all the essential properties of the original PFR, since the Phyllanthus emblica, Linn., is the low cost, freely available plant material. Therefore, the composites could be used as low cost ion-exchangers, when SPEC partly replaces the original PFR up to 20% (w/w) blending without affecting the properties of PFR.